Effect of the modifier on the thermophysical properties of fireproof ethylene-vinyl acetate copolymer composition materials - Chulieieva, Olena; Zolotaryov, Volodymyr (Technology audit and production reserves, 2018)
The object of research is the thermophysical processes of fireproof composite materials: ethylene-vinyl acetate copolymer, which contain fire retardant fillers and a modifier. In order to ensure the incombustibility performance, polymer compositions have a high degree of filling up to 60 % by weight. A copolymer of ethylene with vinyl acetate is used as a polymer matrix. Inorganic fillers-flame retardants are aluminum oxide trihydrate with an average particle diameter of 1.5 μm and 3.0 μm, magnesium oxide dihydrate with an average particle diameter of 3.0 μm and 3.7 μm and hydromagnesite with an average particle diameter of 1.4 μm. One of the most problematic places is the process of processing such compositions. Aminosilane is used as a modifier. Using the method of thermogravimetric analysis and TGA/DSC differential scanning calorimetry, the melting and decomposition temperatures, the crystallinity degree, the specific heat, and the mass loss are determined. The results show that the melting points decrease with increasing modifier content for all samples. A significant decrease in the melting point is observed when using fillers with a large average particle diameter. The temperature of the decomposition beginning increases for all polymer compositions in which the modifier is introduced. The crystallinity degree increases with increasing content of the polymer composition modifier. The specific heat capacity of all polymer compositions increases with an increase in the amount of modifier. This is due to the influence of fillers-flame retardants and modifier on the formation of the structure of polymer compositions. This makes it possible to reduce the melting point by 1.2–16.2 degrees, depending on the chemical composition and dispersion of the flame retardant fillers in the presence of a modifier. The crystallinity degree increases and the specific heat capacity increases with an increase in the modifier content. The decomposition beginning temperature of polymer compositions increases significantly from 20 to 45 degrees. The results will be useful in the development of fireproof formulations of polymer compositions for cable products, taking into account their thermal characteristics.